A redescription of Aculepeira matsudae (Aranei: Araneidae), a species recently found in Far East Russia - Marusik Yu.M.; Omelko M.M.; Simonov P.S. (K M K Scientific Press Ltd, 2022)
Aculepeira matsudae Tanikawa, 1994, a species previously known from Central Hokkaido is reported from Far East Russia for the first time. Previously it was recorded in Khabarovsk and Maritime Provinces as Aculepeira cf. matsudae. The species is redescribed in detail, and an updated diagnosis is provided as well as comparisons with two other species occurring in Far East Russia. The status of species assigned to Aculepeira that occur in the Neotropical Realm is briefly discussed.